Enhanced azo dye biodegradation performance and halotolerance of Candida tropicalis SYF-1 by static magnetic field (SMF). (January 2020) - Tan, Liang; Shao, Yifan; Mu, Guangdi; Ning, Shuxiang; Shi, Shengnan
Highlights: Static magnetic field (SMF) enhanced azo dye decolorization by a yeast SYF-1. Halotolerance of the yeast SYF-1 was also enhanced by 95.0 mT SMF. Activity of lignin peroxidase and laccase was increased by 95.0 mT SMF. Membrane lipid components related to halotolerance regulated due to SMF. Mechanism of SMF-enhancement was proposed through comparative transcriptome. Abstract: Enhancing Acid Red B (ARB) decolorization by growing cells of a halotolerant yeast Candida tropicalis SYF-1 with static magnetic field (SMF) was investigated. Activity of key enzymes and membrane phospholipid fatty acids (PLFAs) were analyzed for estimating the change of metabolic activity and membrane salt-stress response, respectively. Possible enhancement mechanisms were revealed through comparative transcriptome analysis. The results showed that 95.0 mT SMF enhanced ARB decolorization by growing cells of a yeast SYF-1, as well as cell growth and halotolerance capability. Activity of intracellular lignin peroxidase (LiP) and laccase (Lac) was 1.51- and 1.47-fold higher with 95.0 mT SMF than that without SMF, respectively. Unsaturation degree and chain length of dominant PLFAs was increased by 95.0 mT SMF treatment. Several functional protein encoding unigenes related to organics biodegradation, cell growth and halotolerance were 1.17- to 4.19-fold up-regulated in response to 95.0 mT SMF.